Epidemiological and pathogenetic paralels in patients with bronchial asthma in combination with coronary heart disease (review of the literature, observation of the authors) - N. A. Matsegora; E. A. Shkurenko (Kazimierz Wielki University, 2017)
We mate based on the literature review, it is shown the questions epidemiology and pathogenesis paralels in patients with asthma in combination with coronary heart disease. Stresses the leading role of the asthma risk factors contributing to the development of hypoxic conditions and coronary insufficiency. Together with data from the literature review, we also present the results of the study 140 BA patients with concomitant coronary artery disease. It was established that asthma developed in the studied individuals from childhood, and the signs of CHD in 1/3 of them - from a young age. Clinical and epidemiological features of the severity of comorbid pathology in female and male subjects have been revealed. Based on the results obtained, it was concluded that additional methods for the study of the cardiovascular system should be introduced into the diagnostic complex of patients with asthma. The data obtained are the basis for further study of the degree of functional failure of the cardio-respiratory system with a view to further choosing differential treatment.